Interplay of structure, charge-carrier localization and dynamics in copper-silver-bismuth-halide semiconductors - Buizza, LRV; Sansom, HC; Wright, AD; Ulatowski, AM; Johnston, MB; Snaith, HJ; Herz, LM (Wiley, 2021)
Silver-bismuth based semiconductors represent a promising new class of materials for optoelectronic applications because of their high stability, all-inorganic composition, and advantageous optoelectronic properties. In this study, charge-carrier dynamics and transport properties are investigated across five compositions along the AgBiI4–CuI solid solution line (stoichiometry Cu4x(AgBi)1−xI4). The presence of a close-packed iodide sublattice is found to provide a good backbone for general semiconducting properties across all of these materials, whose optoelectronic properties are found to improve markedly with increasing copper content, which enhances photoluminescence intensity and charge-carrier transport. Photoluminescence and photoexcitation-energy-dependent terahertz photoconductivity measurements reveal that this enhanced charge-carrier transport derives from reduced cation disorder and improved electronic connectivity owing to the presence of Cu+. Further, increased Cu+ content enhances the band curvature around the valence band maximum, resulting in lower charge-carrier effective masses, reduced exciton binding energies, and higher mobilities. Finally, ultrafast charge-carrier localization is observed upon pulsed photoexcitation across all compositions investigated, lowering the charge-carrier mobility and leading to Langevin-like bimolecular recombination. This process is concluded to be intrinsically linked to the presence of silver and bismuth, and strategies to tailor or mitigate the effect are proposed and discussed.